Synthesis and Characterization Gold Nanoparticles Using Extracts of Sarang Semut (Myrmecodia pendans) For Sensing of Glucose - Andi Suciati; Abdul Wahid Wahab; Paulina Taba (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Abstract. Gold nanoparticles have been synthesized with simple and relatively safe method by using kaemferol and quercetin containing aqueous extract of Myrmecodia pendans (sarang semut plant). Under this method, it was able to obtain AuNPs and measured the size. The formation of the nanoparticles were identified by the color change (yellow to red) occurred in the chloroauric acid solution after additional aquoeos extract of sarang semut plant. The UV-Visible spectra and particle size analyzer indicated the successful formation of AuNPs with wavelength of 521.5 nm which was stable for 4 days, evidenced by the presence of particles with a size 53.2 nm. XRD analysis showed the difractogram peak of gold nanopartcle. The result of SEM analysis indicated gold nanopartcle surface with spherical and rod-like shapes. Glucose sensor utilized gold nanopartcle as catalyst with measurement range 2–5 mM and regresision 0,868, detection limit of sensor was in concentration 2-5 mM  was 7,5 mM with sensitivity 0,736 A.mM-1.mm-2. Glucose concentration obtained in blood serum was 78,48mg/dL. Gold nanoparticles is promising to detect blood sugar with simply, securely, low cost without using enzyme and harmful material.